Perceptual learning style preferences for learning English literature / Dephy Anak Janggau @ Nyanggau - Janggau @ Nyanggau, Dephy (2015)
English Literature Component was incorporated into the English Language syllabus in March 2000 with the intention to enhance English acquisition among ESL students. Yet, there are concerns over students’ learning success and failure. Factors that may influence students ’ learning achievement have been identified. One of the factors is the students ’ learning styles. Several models o f learning styles have been introduced and one of them is Perceptual Learning Style Preferences (PLSP) which proposes six modes o f learning; visual, auditory, kinesthetic, tactile, group and individual. This research was designed to 1) identify the perceptual learning styles preferences for learning the English literature among Form Five students in Betong, 2) seek the teachers’ perceptions of their students’ perceptual learning style preferences for learning the English literature, 3) find out whether the students ’ perceptual learning style preferences for learning the English literature match with their teachers ’ perceptions o f the students’ perceptual learning style preferences, 4) find out the teachers ’ awareness of their students’ perceptual learning preferences for learning the English literature, and 5) find out the teachers ’ teaching strategies in teaching the English literature. The study involved 207 participants (204 Form Five students and three English language teachers) of a secondary school in Betong. Data were obtained through two methods: questionnaires adapted from Perceptual Learning Style Preferences Questionnaire (PLSPQ) developed by Reid (1987) and semi-structured interviews. The quantitative data were analysed using Statistical Package of Social Sciences (SPSS) version 21, and the qualitative data were analysed using thematic analysis. Among the six perceptual learning styles, the findings show that when learning the English literature, the students prefer group learning style the most and individual learning style the least, in which are concurrent with their teachers ’ perceptions o f the same matters. The teachers are aware of their students ’ preferences and their teaching strategies are geared towards catering to the students’ preferences. The major implication that can be derived from the findings is that being aware and matching up with students ’ learning styles in learning the English literature is very important in ensuring an effective literature teaching and learning process.